EECLA: Clustering and Localization Techniques to Improve Energy Efficient Routing in Vehicle Tracking using Wireless Sensor Networks - Gummadi, Annapurna; K Raghava Rao, Dr (International Journal of Engineering and Technology, 2018)
Abstract: The applications of wireless sensor networks became more usable in daily life. In spite of many proposed techniques and methods, energy efficient routing in WSN is still an open issue. In this paper we made an attempt to give one of the solution for this problem in vehicle tracking system based on the vehicle sensor nodes. We studied many existing works, were failed in handling location and energy efficient routing of vehicle tracking properly. We proposed an algorithm which handles clustering and location at time and improves the performance of the system. This algorithm uses the fundamentals of LEACH, CLAEER and mean shifted algorithm. We conducted a sequence of experiments and our algorithm EECLA (Clustering and Localization Techniques to Improve Energy Efficient Routing in Wireless Sensor Networks) has given better results than the existed one with more accuracy.Â Â